(untitled) (Economic and Political Thought, 2014)
Commune investment constitutes one of the most important factors in local development. It is an important condition for enhancing the implementation of municipal engineering and social services and the growth of the municipal assets, the improvement of the level of services provided in terms of quality and quantity, the creation of conditions for setting up new businesses and the settlement of new inhabitants. There is a common feature of self-governments’ investment – a necessity to involve a certain capital, usually for a long term, which is connected with uncertainty and a risk to achieving the planned benefits. Therefore, it is very important to select appropriate sources of funding and skilful investment project management. There are some typical features and conditions of each source of funding. The self-governments’ task is to select them skilfully so that the effects of tasks implementation are adequate to local communities’ expectations. One of the conditions for achieving the planned aims is an in-depth knowledge of both the mechanisms of raising and possibilities of using their own and additional income as well as repayable sources of funding. The eventual choice of funding sources results from analyses results and the development of alternative funding scenarios. One cannot speak about a universal investment funding structure good for every unit and every project. It depends on various factors connected with the specificity of a given commune, county or voivodeship and the features of the particular investment.